2018
DOI: 10.1111/dme.13636
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin on plasma metabolite profile in the Copenhagen Insulin and Metformin Therapy (CIMT) trial

Abstract: Metformin treatment is associated with decreased levels of valine, tyrosine and carnitine, and increased levels of leucine/isoleucine. None of the identified metabolites can predict the HbA -lowering effect of metformin. Further studies of the association between metformin, carnitine and leucine/isoleucine are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…In summary, we identified dynamic alterations in plasma metabolite concentrations 3 months after LSG in 15 morbidly obese Japanese patients. Although food intake and the changes of medication might affect the plasma metabolite concentrations 28,29 , the present results support LSG as an effective therapeutic strategy for treating obesity not only as a weight loss surgery, but also as a metabolomic intervention 30 . The present findings have the potential to show how LSG ameliorates obesity and present novel therapeutic targets for treating obesity.…”
Section: Discussionsupporting
confidence: 55%
“…In summary, we identified dynamic alterations in plasma metabolite concentrations 3 months after LSG in 15 morbidly obese Japanese patients. Although food intake and the changes of medication might affect the plasma metabolite concentrations 28,29 , the present results support LSG as an effective therapeutic strategy for treating obesity not only as a weight loss surgery, but also as a metabolomic intervention 30 . The present findings have the potential to show how LSG ameliorates obesity and present novel therapeutic targets for treating obesity.…”
Section: Discussionsupporting
confidence: 55%
“…In addition to alterations in lipid and glucose metabolism, there was also evidence of disturbances in some amino acids; levels of two BCAAs, isoleucine and leucine, as well as phenylalanine were higher in women with GDM. Other studies have reported increases in BCAAs and also other amino acids, such as alanine (28) and leucine (7), or decreases in, for example, L‐valine (29) in women with GDM at the time of OGTT. Furthermore, higher levels of leucine and isoleucine have been reported in association with obesity in nonpregnant and pregnant participants (30‐32).…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which GDM per se and its treatment by diet compared with pharmaceutical treatment is related to the metabolic profile is currently poorly understood. In patients with type 2 diabetes, metformin treatment was associated with lower levels of valine and carnitine and higher levels of lysophosphatidylethanolamines as well as elevated concentrations of leucine and isoleucine (7). Another study conducted in participants with coronary disease revealed a decrease in tyrosine and an increase in alanine in patients treated with metformin (8).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several metabolomic techniques were applied to the identification of metabolic signatures associated with T2DM [10,11,12,13,14,15,16,17]. Data in this research field were extensive, revealing new diagnostic/prognostic disease biomarkers [14], or metabolic markers of response to targeted therapies [15,16]. Metabolomics also provided tools for patient’s stratification and recognizable metabolic patterns associated with organ dysfunction [17].…”
Section: Introductionmentioning
confidence: 99%